2014
DOI: 10.1371/journal.pone.0089893
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Isolation in a Patient of Raoultella planticola and Escherichia coli Bearing a Novel ISCR1 Element Carrying blaNDM-1

Abstract: BackgroundThe gene for New Delhi metallo-β-lactamase 1 (NDM-1) has been reported to be transmitted via plasmids which are easily transferable and capable of wide distribution. We report the isolation of two NDM-1 producing strains and possible in vivo transfer of bla NDM-1 in a patient.MethodsClinical samples were collected for bacterial culture and antibiotic susceptibility testing from a patient during a 34-day hospitalization. The presence of bla NDM-1 was detected by PCR and sequencing. Plasmids of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 28 publications
3
31
0
1
Order By: Relevance
“…Similar structures were reported in E. coli and Raoultella planticola isolates from China in a very recent study (13). However, the resistance gene cassettes and genetic arrangement within the complex class 1 integron in PM58 were different from those of pEcNDM1-4, a 58-kb plasmid carrying bla NDM-1 in E. coli, and pRpNDM1-1, a 280-kb plasmid carrying bla NDM-1 in R. planticola (13) (Fig. 1).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Similar structures were reported in E. coli and Raoultella planticola isolates from China in a very recent study (13). However, the resistance gene cassettes and genetic arrangement within the complex class 1 integron in PM58 were different from those of pEcNDM1-4, a 58-kb plasmid carrying bla NDM-1 in E. coli, and pRpNDM1-1, a 280-kb plasmid carrying bla NDM-1 in R. planticola (13) (Fig. 1).…”
supporting
confidence: 79%
“…1). It has been documented that the ISCR1-like elements might be responsible for the mobilization of bla NDM-1 in Enterobacteriaceae and non-Enterobacteriaceae species via the rolling circle replication process (13,15,16). The acquisition of the bla NDM-1 -carrying segment in the complex class 1 integron in PM58 may be related to ISCR1-2, since the oriIS site was identified downstream of this element.…”
mentioning
confidence: 99%
“…ISCR1 has generally been found associated with class 1 integrons, after position 1,313 of the 3=-CS, suggesting integration of circular molecules by recombination in either the 3=-CS or an existing ISCR1 (38). ISCR1 has previously been suggested to be associated with movement of bla NDM (39) and was recently shown to be responsible for mobilizing a region containing bla NDM and part of the 3=-CS, but without the bla DHA ⌬-ampR region, between plasmids (20).…”
Section: Resultsmentioning
confidence: 99%
“…1A). In plasmids from the Enterobacteriaceae, bla NDM genes are generally found in this immediate genetic context, with at least a fragment of ISAba125 containing the Ϫ35 promoter region present upstream, within different length fragments matching Acinetobacter plasmids and associated with different mobile elements (3,(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Partridge and Hall confirmed that a small circular molecule containing ISCR1-dfrA10-sul1 could be transposed into a plasmid within the 3=-conserved sequence (CS) of a cloned class 1 integron in vitro (26). Li et al first identified the circular molecule with ISCR1-bla NDM-1 -3=-CS in a clinical E. coli strain by Southern hybridization (27), and Li et al and Wu et al reported the existence of ISCR1-bla PER-1 -3=-CS in V. cholerae and V. parahaemolyticus using PCR with inverse primers (18,20). In this study, a free circular molecule bearing the ISCR1-bla PER structure was identified in all ISCR1-related isolates by PCR with a pair of inverse primers ( Table 2).…”
Section: Fig 1 Pulsed-field Gel Electrophoresis (Pfge) Profiles Of Prmentioning
confidence: 99%